A refractory metamaterial absorber for ultra-broadband, omnidirectional and polarization-independent absorption in the UV-NIR spectrum. Issue 17 (24th April 2018) - Huang, Yijia; Liu, Ling; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Luo, Xiangang
Abstract : In this paper, efficient ultra-broadband absorption from ultraviolet (UV) to near infrared (NIR) is achieved using a metamaterial perfect absorber (MPA) with refractory constituents. Abstract : In this paper, efficient ultra-broadband absorption from ultraviolet (UV) to near infrared (NIR) is achieved using a metamaterial perfect absorber (MPA) with refractory constituents. Both simulated and experimental results indicate that this proposed MPA exhibits an average absorption over 95% at wavelengths ranging from 200 nm to 900 nm. Besides, owing to the ultrathin thickness and symmetrical topology of this device, it exhibits great angular tolerance up to 60° independent of the incident polarizations. Excellent thermal stability is also demonstrated at high operation temperatures. The physical origin of the ultra-broadband characteristics is mainly based on diffraction/interference engineering at short wavelengths and the anti-reflection effect at long wavelengths. We believe that such a device may find potential applications ranging from photodetection and photothermal energy conversion to ultraviolet protection and thermophotovoltaics.